The woman in the health care professions - Rueda C., Laura (Acta Bioethica, 2006)
This paper tries to establish, through identifying the affective capacities of young women who are studying health care professions, a reflection about the feminine presence in this professional sector. This analysis includes some aspects of the feminine moral development, the vocation to care and to prevent risks and the professional profile that has been developed in careers dedicated to health care.